Improved crowbar protection technique for DFIG using fuzzy logic - Zineb En-nay; Ismail Moufid; Aboubakr El Makrini; Hassane El Markhi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
A doubly-fed induction generator is the most widely used as a wind turbine generator. Due to its drawbacks, doubly fed induction generator (DFIG) is extremely sensitive to grid disturbances, and the fragility of some components which are costly to the producer. Also, its acquisition value is very high in terms of maintenance time or component cost, causing substantial harm to both the energy production and power supplier. It is required that the DFIG components must be protected, especially power electronics devices and DC-Link capacitor. Therefore, this paper presents an improved crowbar strategy for DFIG. This method is based on the AI technique concept of utilizing a fuzzy logic controller. The main goal of this project is to improve the system performance by reducing the dangerous oscillations of electromagnetic torque, DC-link voltage, and rotor current during fault. This work consists of replacing the hysteresis control for the crowbar with fuzzy logic to realize crowbar-FLC. The proposed crowbar is based on free light chain (FLC) depending on rotor currents and DC-link voltage measurements. The control strategy is simulated in the MATLAB Simulink platform to evaluate the efficiency of the suggested technique.